Evaluasi Pengaruh Settling Pond terhadap Kestabilan Lereng Highwall pada Tahap Optimalisasi Penambangan Batubara - Wulandari, Septi Wulandari; Hartawi Riskha (ReTII, 2025)
The slope stability analysis of the highwall of PT. X coal mining was conducted to support the optimization plan for the mining of seams M and N, aiming to obtain coal reserves more efficiently without compromising mine safety. This study aims to evaluate the influence of the existing settling pond on the stability of the highwall slope and to determine the feasibility of the proposed slope geometry design. The analysis was carried out using geotechnical data, including physical and mechanical properties of rocks, discontinuity conditions, and rock mass parameters based on the Rock Mass Rating (RMR) system and Hoek–Brown failure criterion. The Safety Factor (SF) and Probability of Failure (PF) were analyzed under dynamic conditions, considering a seismic acceleration of 0.08 g and groundwater level at 80–85% of the total slope height. The results showed that the minimum SF under dynamic conditions was 1.072, with a PF of 2.608%, which remains above the safety threshold according to the Decree of the Ministry of Energy and Mineral Resources (ESDM) No. 1827 K/30/MEM/2018. These findings indicate that the highwall slope is stable, and the presence of the settling pond has no significant impact on its global stability. Therefore, the optimized slope design can be safely applied in future mining operations.